CDM project for pulp and paper industry of Vietnam - Vo, Viet Cuong (Journal of Technical Education Science, 2017)
The Pulp and Paper industry of Vietnam is a significant emitter of green house gases caused by consumpting much energy in many stage of its operation. Therefore, this industry has many opportunities CDM implementation by the way of saving energy. CDM projects will mitigate emissions and provide significant financial resources contributing to the modernization of the paper industry. The goal for this paper is constructed the processes, methods and identifies opportunities for implementation of CDM projects in Vietnam's paper industry. Proposed method be applied at the factory Tan Mai Paper. The results show that the CDM project for the paper industry has high economic feasibility and open opportunities to reduce emissions to other industries in Vietnam.